Football in the time of COVID-19: Reflections on the implications for the women`s professional league in Colombia - Biram, M. D.; Martinez-Mina, C. Y. (Soccer & Society, 2021)
This article considers the efficacy of the Colombian institutional response to the COVID-19 crisis from a gender perspective. The Colombian Professional Women`s League has been characterized by perpetual crisis since its launch in 2017. Far from the affirmative action needed to remedy its historic marginalization, an environment of conscious institutional inertia had already placed the league in severe doubt before the onset of COVID-19. It is argued that stark asymmetries of power underpin persistent gender differentiation and that an untenable development model has been laid bare and exacerbated by the pandemic.